Habitat utilization of harpacticoid copepods in relation to body forms in a NaGISA rocky shore site in Taklong Island, Guimaras - Lapara, Switzel S.
The Calaparan rocky site in the Taklong Island National Marine Reserve in Guimaras was the study site for the examination of habitat utilization of harpacticoid copepods in relation to body forms in the years 2012 and 2013. Sampling was done following the NaGISA protocol on October 2012 and September 2013 with four 27-meter transect lines laid in different depth gradients namely THT (high tide), TMT (midtide), TLT (low tide) and TST (1 m depth, sub tidal) parallel to the shore. For the harpacticoid body form analysis, meiofauna samples obtained in the ?mid-section? (7, 12 and 17 m) sampling points for both years were accounted in the study. Twenty four families of harpacticoid were identified with Ectinosomatidae as the numerically abundant family comprising 15.96% of the total harpacticoid sampled in both years, followed by Canuellidae (10.27%), Tetragonicipitidae (9.07%), Diosaccidae (7.96%), Metidae (6.84%), Tegastidae (6.62%), Cylindropsyllidae (6.13%), Miraciidae (5.85%), Tisbidae (5.05%) and Thalestridae (4.68%). The overall mean density of harpacticoids in 2012 and 2013 was 19,761 ind. ?m-2 with the average mean density of 9,881 ind. ?m-2 (sd=545.9) between years. In both years, the high tide transect (THT) had the highest mean density of 20,080 ind. ?m-2 whereas the low tide transect (TLT) had the lowest mean density of 19,568 ind. ?m-2. Also, cylindrical body form was dominated by Epibenthic families. Furthermore, two way Analysis of Variance (ANOVA) showed that variability in each tidal level was high, and there was a significant difference (F=7.70, p=0.02) between tidal levels in terms of total harpacticoid abundance however there was no significant difference in harpacticoid abundance between years. Lastly, there was an inverse relationship between the total macroalgal biomass and the overall mean harpacticoid density (R= -0.5921).